Ação bioindicadora da entomofauna em canavial plantado entre aleias de essências florestais nativas - Favetta, Marcela Marques da Silva (Universidade Federal de São Carlos, 2013)
The present work aims to study the acquisition of environmental information through the analysis of insect fauna in an agroforestry system consisting of alleys native trees planted between strips of different widths cultivated with cane sugar. These are important complementary information for the commercial deployment of large areas of this agroforestry system that seeks to mitigate the undesirable impacts caused by sugar cane monoculture. The option for this type of analysis is linked to the practical and low cost, using simple equipment, apply without interfering with routine activities of production or the development of culture. Another aspect is the possibility of obtaining information in the short term, considering the insects are sensitive to environmental stimuli, numerous and capable of producing several generations in a short period of time. Besides that respond quickly to disturbances in their habitat features and changes in structure and function of ecosystems. Catches of the specimens were held bimonthly and lines of trees, and the tracks in culture for three complete cycles of cane sugar. We analyzed the interactions of these populations in relation to climatic aspects and between different environments formed by sugar cane planted between three different species of native trees; guapuruvu, cedar and yellow ipe. Were captured 84,644 specimens, and their records used in ecological analyzes. The results showed that initially environments formed by different combinations of tree-cane behaved differently. During studies of these environments were coalescing gradually showing a tendency to operate in the future as a single community without major conflicts. This would be a desirable feature about the purpose of implementing such agroforestry system. The spatial distribution of insect fauna occurred randomly in all environments studied. Environmental analysis with relatively simple methodology has generated consistent information.
Action of bioindicator entomofauna sugarcane planted in between alleys native forest species
Keywords: Cana-de-açúcar; Aleias; Florestas nativas; Bioindicadores; CIENCIAS AGRARIAS